A very-high-energy component deep in the γ-ray burst afterglow - Abdalla, Hassan; Bernlöhr, Konrad; Hinton, James Anthony; Hofmann, Werner; Jankowsky, Felix; Marx, Ramin; Quirrenbach, Andreas; Rieger, Frank M.; Schwemmer, Stephanie; Völk, Heinrich J. (Nature, 2019)
Very-high-energy γ-rays observed ten hours after the prompt emission of the γ-ray burst 180720B can be attributed to either an inverse Compton or an extreme synchrotron process.
Gesehen am 20.01.2020